Reducing Students’ Public Speaking Anxiety with Gamification Methods - Alice Kirana Ammara Aqila; Moh. Sholeh (International Conference on Sustainable Health Promotion, 2025)
Fear of public speaking is a challenge for junior high school students. This study aims to reduce students’ fear of public speaking through gamification. This study used a single-group pretest-posttest design with 10 students selected purposively. The instruments used included a questionnaire, a Public Speaking Anxiety Scale, and observations. This intervention used prompt cards as a game-based medium for speaking practice. Data analysis using a paired-sample t-test showed a significant difference between pretest and posttest scores, with an effect size of 1.33, which is categorized as large. These findings indicate that gamification is effective in increasing students’ confidence in public speaking and can be an alternative strategy for teachers in teaching speaking skills.